2021
DOI: 10.3390/biomedicines10010069
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Enriched Exosomes from Different Sources of Mesenchymal Stem Cells Can Differentially Modulate Functions of Immune Cells and Neurogenesis

Abstract: Adult Mesenchymal stem cells-derived exosomes carry several biologically active molecules that play prominent roles in controlling disease manifestations. The content of these exosomes, their functions, and effect on the immune cells may differ depending on their tissue sources. Therefore, in this study, we purified the exosomes from three different sources and, using the RNA-Seq approach, highly abundant microRNAs were identified and compared between exosomes and parental cells. The effects of exosomes on dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…Based on the important roles played by miRNAs in regulating the expression of several genes, miRNA-based therapeutic potential of stem cells is introduced as a vital therapeutic option for multiple diseases [ 98 ]. Importantly, our results lie in accordance with previous studies, which showed some common miRNAs derived from exosomes or EVs derived from mesenchymal stem cells regulate different functions in various diseases [ 29 , 99 , 100 , 101 ].…”
Section: Discussionsupporting
confidence: 93%
“…Based on the important roles played by miRNAs in regulating the expression of several genes, miRNA-based therapeutic potential of stem cells is introduced as a vital therapeutic option for multiple diseases [ 98 ]. Importantly, our results lie in accordance with previous studies, which showed some common miRNAs derived from exosomes or EVs derived from mesenchymal stem cells regulate different functions in various diseases [ 29 , 99 , 100 , 101 ].…”
Section: Discussionsupporting
confidence: 93%
“…Briefly, bone marrows were collected from the donors ( n = 3) undergoing the routine medical test procedure at AIIMS, New Delhi. The MSCs were isolated and cultured as described previously by our group 30 . Briefly, MSCs were passaged and identified by surface marker analysis and in vitro differentiation assays 31 .…”
Section: Methodsmentioning
confidence: 99%
“…Mesenchymal stem cell isolation and exosome purification were performed at the Stem Cell Facility, All India Institute of Medical Sciences (AIIMS), New Delhi, using a previously standardized protocol. 29 , 30 Briefly, bone marrows were collected from the donors ( n = 3) undergoing the routine medical test procedure at AIIMS, New Delhi. The MSCs were isolated and cultured as described previously by our group.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, it has become clearer and clearer that, in addition to genetic and epigenetic control, signaling from the tissue environment (mechano-transduction and molecular cues) [96][97][98] and/or from cargo proteins/RNAs in the shuttle, secreted vesicles (exosomes) contribute to the regulation of cell and tissue growth, differentiation and migration [99]. Cell shaping and formation of cellular processes, such as the neuronal growth cone [100], are crucial to sensing (and responding to) such tissue environmental stimuli.…”
Section: Traffic At a Glancementioning
confidence: 99%